The effectiveness of sexual and reproductive health (SRH) education programme among secondary school students in Felda, Pahang - Abd. Aziz, Karimah Hanim; Ab Rahman, Azriani; Salleh, Halim; Osman, Iskandar Firzada; Nik Mohamed, Mohamad Haniki; Draman, Samsul (2014)
Objective: The objective of the study was to assess the effectiveness of Sexual and Reproductive Health (SRH) Education program in improving the knowledge on sexual and reproductive health, attitude towards sexual and reproductive health and practice of premarital sexual activities among early adolescents from Felda schools in Pahang, Malaysia.